THE INFLUENCE OF SELF-CONGRUITY AND MOBILE MARKETING ON BRAND LOYALTY AT FAST FOOD RESTAURANTS CALIFORNIA CHICKEN IN SUBANG CITY - Didi Junaedi; Gugyh Susandy; Devy Widya Apriandi (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2019)
The purpose of this research is to know Self-Congruity and Mobile Marketing at fast food restaurant California Fried Chicken. And to know the influence of each variable either partially or simultaneously, Self-Congruity (X1) and Mobile Marketing (X2) to Brand Loyalty (Y).The method in this research using descriptive method of analysis. With sample number 100 respondents with sampling using purposive sampling technique. The data obtained from this research is the interval scale with the analysis method using multiple linear regression analysis. Based on the results say that Self-Congruity has a positive and significant effect on Brand Loyalty, Mobile Marketing have a positive and significant impact on Brand Loyalty. And Self-Congruity and Mobile Marketing influence as much as of Brand Loyalty.